If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3x + -6) = 72 Reorder the terms: -2(-6 + 3x) = 72 (-6 * -2 + 3x * -2) = 72 (12 + -6x) = 72 Solving 12 + -6x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -6x = 72 + -12 Combine like terms: 12 + -12 = 0 0 + -6x = 72 + -12 -6x = 72 + -12 Combine like terms: 72 + -12 = 60 -6x = 60 Divide each side by '-6'. x = -10 Simplifying x = -10
| 36x^4-60x^2y^3+25y^6= | | 3e=8.4 | | 6s+-3+(s+7)+7s+-12= | | -2(x+1)=10x | | 2b+b+5b=18324 | | -7x+8=3x-12 | | Y=80+(-1.2)x | | -7+8=3x-12 | | -(-2r+4s)= | | F(x)=-5x^2-8x | | X^2+7x+6=(x+6) | | 10x+25=5+12x | | 2d-15.8=3.7+d | | 3/5×Y-3=12 | | ?/3x1111 | | X=-21.5+7.5(4) | | 5+0.6666666=4x+7 | | 4x-13=1/2x-4 | | 18m^5+48m^3+32m= | | (10y)-4=156 | | 2x-15y=-43 | | -0.3=log(x) | | x+0.26x=170 | | -0.3=logx | | j-5j-36=0 | | t=7(7)-4 | | W-2=6+3w | | 8+3w-w-3= | | 13-8x=53 | | y=24337x-4E+07 | | 18y-5=x+10 | | -7/4x=7 |